A comparison of psychodynamic measures of level of oedipal functioning and of object relations in bulimic versus drug dependent women - Aber, Diana (My University, 2016)
No abstract provided.
A dissertation submitted to the Faculty of Arts, University of the Witwatersrand, in partial fulfilment of the requirements for the Degree of Master of Arts, Clinical Psychology. Johannesburg, September 1992
Keywords: Bulimia -- South Africa.; Drug abuse -- South Africa.; Psychodynamic psychotherapy -- South Africa.; Women -- Mental health -- South Africa.